Analisis Tingkat Kualitas Produk dan Tingkat Pelayanan Kentucky Fried Chicken (KFC) Cabang Palembang Trade Centre - Santi Oktavianti (JURNAL MANAJEMEN DAN BISNIS SRIWIJAYA, 2018)
Tujuan penelitian – This research to identify and analyze the level of product quality and service level of Kentucky Fried Chicken (KFC) branch of the Palembang Trade Center Desain/Metodologi/Pendekatan – The variables used in this study is the level of product quality and service quality levels. The analytic technique used in this research is descriptive quantitative analysis Temuan – Based on the survey result revealed that the analysis of the level of product quality and service level of Kentucky Fried Chicken (KFC) in Palembang Branch Trade positive effect on service, this sesuiai with the consumer demand in expect include: KFC halal certified chicken, flavored chicken meat that is tender and delicious, as well as the packaging of products is good. Based on the results of the quality of service, consumers are comfortable with employees who are always friendly when ordering food and sprightly in helping consumers, as well as adequate facilities such as air conditioning, clean Restrooms, free parking and there are several restaurants in the arena children's play area Keterbatasan penelitian – Originality/value – Keywords : The level of product quality and service level